Wideband CMOS Receivers - Fernandes, Miguel D; Oliveira, Luis B (New York: Springer, 2015)
This book demonstrates how to design a wideband receiver operating in current mode, in which the noise and non-linearity are reduced, implemented in a low cost single chip, using standard CMOS technology. The authors present a solution to remove the transimpedance amplifier (TIA) block and connect directly the mixer's output to a passive second-order continuous-time [sigma][increment] analog to digital converter (ADC), which operates in current-mode. These techniques enable the reduction of area, power consumption, and cost in modern CMOS receivers.
Keywords: Electronic circuits; Electronics; Microelectronics; Microprocessors; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Processor Architectures